(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
This article analyzes the theoretical and conceptual foundations for the implementation of innovative information technologies in ensuring state border security. The study scientifically substantiates the role of digital ecosystems, artificial intelligence, and Big Data in border management, as well as the significance of a proactive approach in ensuring security. Furthermore, the article examines modern technological solutions aimed at improving the efficiency, responsiveness, and reliability of border protection systems under contemporary security challenges.